Novel approaches to quality control and harmonisation of analysers within a veterinary laboratory system - Daly, Susan (2024)
The purpose of the research project was to develop a novel laboratory quality system to harmonise the five separate laboratories operating a commercial diagnostic service. Methods for initial and ongoing maintenance of harmonisation of haematology analysers within the laboratories were developed and implemented.